Process Analytical Technologies (PAT)—the impact for Process Systems Engineering - Chen, Zeng Ping; Lovett, David; Morris, Julian (Computer Aided Chemical Engineering, 2008)
With the increasing take-up of Process Analytical Technologies (PAT) by the pharmachem, bio-pharma, specialty chemicals and materials manufacturing industries there is a critical need for robust data verification, particularly as this information is being included in real-time control or at least advisory feedback applications. In particular the accuracy and reliability of spectral calibrations for processes which are subject to variations in physical properties such as sample compactness, surface topology, etc are becoming a hot topic The variation in the optical path-length materializing from the physical differences between samples may result in multiplicative light scattering influencing spectra in a nonlinear manner leading to the poor calibration performance. In this paper a number of new approaches are shown to overcome the limitations of existing methods and algorithms. Space precludes detailed descriptions of the new algorithms, which are fully referenced, with some of the main results being presented and the justification why these data validity issues need to be addressed by the Process Systems Engineering and CAPE communities.